Uwagi o regulacji prawnej umieszczania niepoczytalnych sprawców czynów zabronionych w zakładach psychiatrycznych na marginesie pracy M . Pyrcak-Górowskiej „Detencja psychiatryczna orzekana jako środek zabezpieczający w świetle badań aktowych” - Góralski, Piotr (Kwartalnik Prawa Publicznego, 2017)
This article is a review of Mrs. Pyrcak-Górowska’s doctoral thesis devoted to the normative bases and the practical aspects of the court practice of application of the isolation-therapeutic preventive measure – placing criminal offenders recognised as insane in psychiatric facilities. The review included in the article constitutes an opportunity to dispute some of the author’s views on the legal bases of applying the above mentioned preventive measure, in particular on the feasibility of determining the perpetrator (i.e. the motives prompting the perpetrator’s actions and intentions) of the offence subject to psychiatric detention, on the legitimacy of applying the principle lex retro non agit to preventive measures, or on the feasibility of assessing the probability of recidivism as very high in offenders recognised as insane. The article, references have been also made to selected issues from law of criminal proceedings and criminal executory law on adjudicating and applying psychiatric detention as a preventive measure.